Verification of In Situ Thresholds and Integrated Real-Ear Measurements. - DiGiovanni, Jeffrey J.; Pratt, Ryan M. (Journal of the American Academy of Audiology, 2010)
Background: Accurate prescriptive gain results in a more accurate fit, lower return rate in hearing aids, and increased patient satisfaction. In situ threshold measurements can be used to determine required gain. The Widex Corporation uses an in situ threshold measurement strategy, called the Sensogram. Real-ear measurements determine if prescriptive gain targets have been achieved. Starkey Laboratories introduced an integrated real-ear measurement system in their hearing aids. Purpose: To determine whether the responses obtained using the Widex Sensogram were equivalent to those obtained using current clinical threshold measurement methods. To determine the accuracy of the Starkey IREMS™ (Integrated Real Ear Measurement System) in measuring RECD (real-ear to coupler difference) values compared to a dedicated real-ear measurement system. Research Design: A verification design was employed by comparing participant data measured from standard, benchmark equipment and procedures against new techniques offered by hearing-aid manufacturers. Study Sample: A total of 20 participants participated in this study. Ten participants with sensorineural hearing loss were recruited from the Ohio University Hearing, Speech, and Language Clinic participated in the first experiment. Ten participants with normal hearing were recruited from the student population at Ohio University participated in both experiments. The normal-hearing group had thresholds of 15 dB HL or better at the octave frequencies of 250-8000 Hz. The hearing-impaired group had thresholds of varying degrees and configurations with thresholds equal to or poorer than 25 dB HL three-frequency puretone average. Data Collection and Analysis: The order of measurement method for both experiments was counterbalanced. In Experiment 1, thresholds obtained via the Widex Sensogram were compared to thresholds obtained for each participant using a clinical audiometer and ER-3A insert ear phones. In Experiment 2, RECD values obtained via the Starkey IREMS were compared to RECD values obtained via the Audioscan Verifit™. A repeated-measures analysis of variance (ANOVA) was used for statistical analysis, and a Fisher's LSD (least significant difference) was used as a post hoc analysis tool. Results: A significant difference between Sensogram thresholds and conventional audiometric thresholds was found with the Sensogram method resulting in better threshold values at 0.5, 1.0, and 2.0 kHz for both groups. In Experiment 2, a significant difference between RECD values obtained by the Starkey IREMS and the Audioscan Verifit system was found with significant differences in RECD values found at 0.25, 0.5, 0.75, 1.5, 2.0, and 6.0 kHz. Conclusions: The Sensogram data differ significantly from traditional audiometry at several frequencies important for speech intelligibility. Real-ear measures are still required for verification of prescribed gain, however, calling into question any claims of shortened fitting time. The Starkey IREMS does perform real-ear measurements that vary significantly from benchmark equipment. These technologies represent a positive direction in prescribing accurate gain during hearing-aid fittings, but a stand-alone system is still the preferred method for real-ear measurements in hearing-aid fittings.